Respuesta :

qabtt

Remember Heron's formula, which states the following:

[tex]A = \sqrt{s(s - a)(s - b)(s - c)}[/tex]

  • [tex]s = \dfrac{a + b + c}{2}[/tex]
  • [tex]a[/tex], [tex]b[/tex], and [tex]c[/tex] are the side lengths of the triangle

In this case, we can say [tex]\overline{AB} = \overline{BC} = \overline{AC} = a[/tex].


Thus,

[tex]s = \dfrac{a + a + a}{2} = \dfrac{3a}{2}[/tex],


Now, let's apply this to Heron's formula:

[tex]A = \sqrt{\Big( \dfrac{3a}{2} \Big) \Big( \dfrac{a}{2} \Big) ^3}[/tex]


Now, let's try to simplify this expression if possible.

[tex]A = \sqrt{\Big( \dfrac{3a}{2} \Big) \Big( \dfrac{a}{2} \Big) ^3}[/tex]

[tex]A = \sqrt{\Big( \dfrac{3a}{2} \Big) \Big( \dfrac{a^3}{8} \Big)}[/tex]

[tex]A = \sqrt{\dfrac{3a^4}{16}}[/tex]

[tex]A = \sqrt{\dfrac{3}{16}} \cdot \sqrt{a^4}[/tex]

[tex]A = a^2 \sqrt{\dfrac{3}{16}}[/tex]

[tex]A = a^2 \sqrt{\dfrac{3}{4}} \cdot \sqrt{\dfrac{1}{4}}[/tex]

[tex]A = a^2 \dfrac{\sqrt{3}}{2} \cdot \dfrac{1}{2}[/tex]

[tex]A = \dfrac{a^2 \sqrt{3}}{4}[/tex]


Our answer is [tex]\boxed{A = \dfrac{a^2 \sqrt{3}}{4}}[/tex].